Global change explains reduced seeding in a widespread New Zealand tree: indigenous Tūhoe knowledge informs mechanistic analysis - Yukich Clendon, Oscar M. M.; Carpenter, Joanna K.; Kelly, Dave; Timoti, Puke; Burns, Bruce R.; Boswijk, Gretel; Monks, Adrian (Frontiers in Forests and Global Change, 2023)
Introduction Climate change is expected to exacerbate the pressures faced by already fragile ecosystems. Negative impacts on the localized and culturally significant plant and animal species within these ecosystems will have cascading effects for the indigenous communities that interact with those species. Understanding how climate change affects culturally important seed crops may be particularly important, as seeds are critical for forest regeneration as well as providing sustenance for wildlife and people. In the central North Island/Te Ika-a-Māui of Aotearoa-New Zealand, Tūhoe elders of the Tuawhenua region have observed declines in seed production by the large-fruited locally dominant forest tree Beilschmiedia tawa (tawa, Lauraceae) over the last half century, which could be related to climate change. Methods We used seed trap data from six sites throughout the geographic range of tawa to measure trends in seed crop size from 1986 to 2020 and to determine which weather factors affect seed crops. We then used these weather predictors to hindcast how tawa seeding may have changed in Tuawhenua forests from 1910–2019, based on historic weather data. Results Seed trap data showed a decline in seeding through time across tawa’s range, and that seeding was lower at more northerly sites. Seed crops were synchronous among trees within sites, but were strongly asynchronous among sites. High seed crops were associated with cooler summer and winter temperatures, and with high rainfall. In the Tuawhenua region, increases in summer and winter temperatures appear to have contributed to the declines in tawa seed crops observed by elders, with the model predicting that years with heavy fruiting have become less frequent after 1940. Discussion Our study provides strong evidence that tawa is undergoing changing seedfall patterns in response to changing climate. The biggest weather drivers of seeding that we identified in tawa were winter and summer temperature, both of which were negatively associated with crop size. Both winter and summer temperatures have increased in Tuawhenua in the last 100 years suggesting a possible mechanism to explain observations of long-term declines in tawa seedfall observed by Tūhoe elders of the Tuawhenua region, with ecological and cultural implications.